IMF Survey : Volume 29, Issue 17. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2000)
In a press release issued on August 18, the IMF Executive Board announced that on August 3 it had discussed making the independent Evaluation Office operational (see Press Release No. 00/27) and agreed to the publication of the background paper that provided the basis for the discussion, as well as the Chairman's concluding remarks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet